2005
DOI: 10.1002/jts.20039
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in mental health treatment following the World Trade Center Disaster: Implications for mental health care and health services research

Abstract: To assess disparities in mental health treatment in New York City (NYC) after the World Trade Center Disaster (WTCD) reported previously related to care access, we conducted analyses among a cross-sectional survey of adults who had posttraumatic stress disorder (PTSD) or major depression (N = 473) one year after the event. The dependent variables examined were use of mental health services, in general, and use of mental health services related to the WTCD. Similar dependent variables were developed for medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
57
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 42 publications
9
57
1
1
Order By: Relevance
“…Further, we chose to analyze Jews and Arabs separately due to their many differences, and studies that analyze combined samples will reveal different kinds of findings that are more generalizable across cultures. Our cooperation rates are similar to other studies (Bonanno, Galea, Bucciarelli & Vlahov, 2006;Boscarino, Adams, Stuber, & Galea, 2005), but we must consider that nonresponders may be different in important ways that cannot be discerned. Nonresponders may include both those who are more socially adapted and therefore at work more hours, or those more maladapted, who decline being interviewed, or otherwise cannot be reached.…”
Section: Discussionsupporting
confidence: 84%
“…Further, we chose to analyze Jews and Arabs separately due to their many differences, and studies that analyze combined samples will reveal different kinds of findings that are more generalizable across cultures. Our cooperation rates are similar to other studies (Bonanno, Galea, Bucciarelli & Vlahov, 2006;Boscarino, Adams, Stuber, & Galea, 2005), but we must consider that nonresponders may be different in important ways that cannot be discerned. Nonresponders may include both those who are more socially adapted and therefore at work more hours, or those more maladapted, who decline being interviewed, or otherwise cannot be reached.…”
Section: Discussionsupporting
confidence: 84%
“…The author and his colleagues concluded that those who were directly exposed as compared to those who were indirectly exposed to the attacks were more likely to experience a higher prevalence of psychological problems. The study showed that those residents with the greatest exposure to the WTC events exhibited overall poor mental and physical health (Adams and Boscarino 2005a).…”
Section: New York City/ Adult Populationmentioning
confidence: 99%
“…Results showed that adults 45-64 years of age and those who had experienced panic attacks were the most likely to use medications. Open-ended questions revealed that the major barrier to the delay in seeking treatment was related to access issues (Boscarino et al 2005a).…”
Section: New York City/ Adult Populationmentioning
confidence: 99%
“…However, increased MHS utilization does not necessarily mean that all victims seek immediate treatment or sought treatment within a few months after the disaster. Boscarino, Adams, Stuber, and Galea (2005), for example, reported that in the first 12 months after the 9/11 terrorist attacks, 55% of New Yorkers with PTSD or depression had not used MHS. Early detection may enhance activities aimed at stimulating disaster victims with these health problems to use mental health services.…”
mentioning
confidence: 99%